The Effect of Institutional Relocation on Employee Work Discipline at State Islamic University Imam Bonjol Padang: The Mediating Role of Work Motivation - Renil Septiano; Deni Erianto (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study examines the effect of institutional relocation on employee work discipline at State Islamic University Imam Bonjol Padang and tests the mediating role of work motivation. The study employed a quantitative explanatory design with a cross-sectional survey approach. From a population of 184 employees, 70 permanent employees were selected through accidental sampling. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS. The results show that institutional relocation has a significant negative effect on work motivation, but a significant positive effect on work discipline. Work motivation does not significantly affect work discipline and does not mediate the relationship between institutional relocation and work discipline. These findings indicate that institutional relocation may create psychological adjustment pressure while simultaneously strengthening employee discipline through more organized work arrangements, improved facilities, and clearer work procedures. The study contributes to organizational behavior research by showing that organizational change in a public Islamic university does not necessarily influence discipline through motivational mechanisms. Practically, post-relocation policy should prioritize facilities, change communication, psychological support, and employee readiness.